High hydrostatic pressure processing to replace texturizing agents on a plant product intended for altered deglutition: A concept proof. (15th April 2023) - Fernández-Pan, Idoya; Merino, Gorka; Virseda, Paloma; Beriain, María José; Ibañez, Francisco C.
Abstract: High hydrostatic pressure processing (HPP) can cause changes in food texture. These changes can be beneficial when developing food with strict texture specifications as it is the case of food targeted to people with altered deglutition (AD) issues. The aim of the present research was to evaluate the HPP potential as an alternative to the use of texturizing agents currently added to AD-targeted food products. First, formulation and experimental conditions of treatments were established, and 2 types of chickpea protein purées, one containing corn starch (PS) and the other chicory inulin (PI), were developed. Second, the purées were, in one case HPP-treated (300–400 MPa; 3–9 min) and in the other texturized with agar-agar and xanthan gum. Overall, HPP did not significantly affect the proximate composition of the purées and improved their microbiological quality, and, most importantly, they caused beneficial texture changes on both PS and PI purées. In addition, HPP-treatments conferred similar instrumental texture values to texturized purées. These texture values come within the given specific range data supplied by the literature for AD suitability. The present study provides the basis for applying HPP in the development of texturizer-free AD-oriented purées. Highlights: HPP is an appropriate technology to modify the texture of foods. HPP has potential to develop plant-based purées for altered deglutition. Purée's texture response to HPP is formulation-dependent. HPP preserves the nutritional values of purées targeted to altered deglutition. HPP to avoid the addition of texturizers in purées formulation.